Police Stress, Mental Health, and Resiliency during the COVID-19 Pandemic - Stogner, John (American journal of criminal justice, 2020)
The COVID-19 pandemic created social upheaval and altered norms for all members of society, but its effects on first responders have been particularly profound. Law enforcement officers have been expected to coordinate local shutdowns, encourage social distancing, and enforce stay-at-home mandates all while completing the responsibilities for which they are already understaffed and underfunded. The impact of the COVID-19 pandemic on officer stress, mental health, resiliency, and misconduct is explored drawing insight from reactions to the HIV epidemic over two decades earlier and the terrorist attacks of September 11, 2001. COVID-19 policing is hypothesized to serve as a significant stressor for officers and compound the general and organizational stress associated with the occupation. Avenues for providing officer support are discussed and recommendations for research into the phenomenon presented.